11C-PIB PET imaging reveals that amyloid deposition in cases with early-onset Alzheimer’s disease in the absence of known mutations retains higher levels of PIB in the basal ganglia - Youn YC (Dove Medical Press, 2017)
Young Chul Youn,1 Jae-Won Jang,2 Su-Hyun Han,1 HyeRyoun Kim,3 Ju-Won Seok,4 Jun Soo Byun,5 Kwang-Yeol Park,1 Seong Soo A An,6 In Kook Chun,7 SangYun Kim8 1Department of Neurology, Chung-Ang University College of Medicine, Seoul, 2Department of Neurology, Kangwon National University Hospital, 3Department of Laboratory Medicine, 4Department of Nuclear Medicine, 5Department of Radiology, Chung-Ang University College of Medicine, 6College of Bionano Technology, Gachon Bionano Research Institute, Gachon University, 7Department of Nuclear Medicine, Kangwon National University Hospital, 8Department of Neurology, Seoul National University Bundang Hospital and Seoul National University College of Medicine, Gyeonggi-do, Republic of Korea Purpose: Early-onset Alzheimer’s disease (EOAD) has a different pathologic burden and clinical features compared with late-onset Alzheimer’s disease (LOAD). We examined the effects of age at onset on the burden and distribution of β-amyloid in patients with EOAD, in whom well-characterized mutations associated with Alzheimer’s disease were absent.Methods: We genotyped ApoE, APP, PSEN1 and PSEN2 in the patients with Alzheimer’s disease: 9 patients with EOAD (age <65), 11 with LOAD (age >70) and 8 normal controls (NCs), all of whom had undergone 11C-labeled Pittsburgh compound B-positron emission tomography imaging.Results: Patients with EOAD exhibited higher z scores and larger cluster sizes, and retained higher levels of Pittsburgh compound B in the bilateral thalamus and in some parts of the globus pallidus (P<0.05, false discovery rate).Conclusion: Distribution of amyloid deposition in EOAD outside the context of genetic mutations topographically showed some differences from that in LOAD. Keywords: Alzheimer’s disease, early-onset Alzheimer’s disease, amyloid PET, basal ganglia, Pittsburgh compound B, amyloid